2018
DOI: 10.1155/2018/1035871
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Worksite Wellness Nutrition and Physical Activity Programs and Their Subsequent Impact on Participants’ Body Composition

Abstract: Background Adult obesity is globally recognized as a public health concern. As adults spend most of their weekdays at work, worksite wellness programs may include topics of nutrition education and physical activity to improve an employee's body composition. However, results are inconsistent with the impact they have on employees' body composition. Objective The purpose of this systematic review was to evaluate worksite wellness nutrition and physical activity programs and their subsequent impact on participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 85 publications
(222 reference statements)
0
12
0
Order By: Relevance
“…These data contrast with a systematic review conducted in 2016 by Schoeppe et al [10], in which they reported that virtual interventions were not effective in increasing PA levels. Possibly, the fact that all the participants were predisposed to change and were always supervised by a professional could have influenced the results of the present study [13][14][15]. On the other hand, both groups increased PA levels in the same way, even though during the COVID-19 pandemic in which the RSEG participants were, PA levels decreased among the general population [19,20,54].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…These data contrast with a systematic review conducted in 2016 by Schoeppe et al [10], in which they reported that virtual interventions were not effective in increasing PA levels. Possibly, the fact that all the participants were predisposed to change and were always supervised by a professional could have influenced the results of the present study [13][14][15]. On the other hand, both groups increased PA levels in the same way, even though during the COVID-19 pandemic in which the RSEG participants were, PA levels decreased among the general population [19,20,54].…”
Section: Discussionmentioning
confidence: 65%
“…The participants in this study achieved long-term adherence to a healthy lifestyle, which could be partly because they were predisposed to change [14], and had psychological support since nutritional barriers and motivation to change were addressed during the workshops [13,15]. Also, before starting the intervention the participants became aware of their unhealthy lifestyle habits and their possible repercussions on the development of NCDs through a detailed report that was given to them [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reutman [8] Sandercock [10], in 2018, conducted a systematic review to evaluate WHP programs on physical activity and nutrition and their impact on workers' body composition. It analyzed 23 studies: 21 articles measured BMI (kg/m 2 ), 7 measured weight (kg), 6 measured % body fat and 3 measured waist circumference (cm), a predictor of cardiovascular (CV) risk.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, awareness of potential health problems leads to more favorable attitudes toward personalized nutrition [ 6 , 7 ]. Workforce wellness programs appear to be more effective if the content is tailored to participants’ needs [ 8 ]. Thus, personalized nutrition approaches may be more effective in changing dietary and other lifestyle behaviors, ultimately improving health outcomes, as compared to guidelines derived for the majority of the population [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%